The European Union is proposing that 10% of natural and semi-natural habitats in agricultural landscapes be conserved - CGIAR Research Program on Water, Land and Ecosystems (2020)
Agricultural landscape biodiversity targets were included in the European Union Biodiversity Strategy for 2030, reflecting the ambition of the Convention on Biological Diversity